The Prevalence of Cariogenic Salivary Micro-Organisms in Children of Various Ages - Enita Nakaš; Amila Zukanović (Biomolecules & Biomedicine, 2007)
The objective of the research was to obtain data on the values of salivary Streptococcus mutans and Lactobacillus spp. in 12 years old children and teenagers (13 - 18 years old children), and to compare the values of these cariogenic microoorganisms in children of various ages, for the purpose of valuating the risk of caries. The sample comprised 32 persons divided into two groups. The first group included 17 children of the age of 12. The second group included 15 teenagers. The specimen of stimulated saliva, needed for the purpose of establishing the quantities of Streptococcus mutans and Lactobacillus spp., was taken by the method of CRT’-bacteria, according to manufacturers instruction. In the group of 12 years old children, the distribution of salivary Lactobacillus spp. was as follows: very low values 41,1%, low values 35,2%, high values 17,6%, very high values 5,8%, while in the group of teenagers, the results were the following: very low values 26,66%, low values 33,33%, high values 40%, very high values 0%. The levels of Streptococcus mutans were the following: 12 years old children had very low values in 41,7% cases, low values in 11,7% cases, high values in 41,7% cases, very high values in 5,8% cases, while the group of teenagers had very low values in 0%, low values in 33,3%, high values in 33,3%, and very high values in 33,3% cases. The levels of Streptococcus mutans are higher in our teenage children than in younger children, while the differences in levels of Lactobacillus spp. among children of various ages do not exist. In terms of global distribution, the levels of Streptococcus mutans and Lactobacillus spp. are higher in our population than in other countries in both control groups.